RNase L Levels in Peripheral Blood Mononuclear Cells: 37-Kilodalton/83-Kilodalton Isoform Ratio Is a Potential Test for Chronic Fatigue Syndrome - Tiev, Kiet Phong (American Society for Microbiology, 2003)
Chronic fatigue syndrome (CFS) is a disorder characterized by debilitating fatigue associated with immunological abnormalities. The etiology remains unclear. A low-molecular-mass (37 kDa) isoform of RNase L has been described in peripheral blood mononuclear cell (PBMC) extracts, and the ratio of two isoforms of RNase L (37 kDa/83 kDa) has been proposed as a potential biochemical marker of CFS. In a prospective case-control study, we tested whether the RNase L 37-kDa/83-kDa ratio could discriminate a SFC population. We compared the ratio of RNase L isoforms in PBMCs from 11 patients with CFS (6 women and 5 men; mean age ± standard deviation, 43.2 ± 13.8 years) and PBMCs from 14 healthy well-matched volunteers (10 women and 4 men; age, 39.1 ± 11.6 years). A ratio of RNase L of 0.4 used as a threshold allowed diagnosis of CFS with high sensitivity (91%; 95% confidence interval [CI], 57 to 99%) and specificity (71%; 95% CI, 41 to 90%). The positive and negative prognostic values were 71% (95% CI, 41 to 90%) and 91% (95% CI, 57 to 99%), respectively. In the absence of acute infection or chronic inflammation, a high RNase L ratio could distinguish CFS patients from healthy volunteers. Additional large studies and follow-up studies are required to confirm the stability of this high ratio of RNase L isoforms in a CFS group.